Global Variation of Nutritional Status in Children Undergoing Chronic Peritoneal Dialysis: A Longitudinal Study of the International Pediatric Peritoneal Dialysis Network - Schaefer, Franz; Benner, Laura; Borzych-Dużałka, Dagmara; Zaritsky, Joshua; Xu, Hong; Rees, Lesley; Antonio, Zenaida L; Serdaroglu, Erkin; Hooman, Nakysa; Patel, Hiren; Sever, Lale; Vondrak, Karel; et al. (Scientific reports, 2019)
While children approaching end-stage kidney disease (ESKD) are considered at risk of uremic anorexia and underweight they are also exposed to the global obesity epidemic. We sought to investigate the variation of nutritional status in children undergoing chronic peritoneal dialysis (CPD) around the globe. The distribution and course of body mass index (BMI) standard deviation score over time was examined prospectively in 1001 children and adolescents from 35 countries starting CPD who were followed in the International Pediatric PD Network (IPPN) Registry. The overall prevalence of underweight, and overweight/obesity at start of CPD was 8.9% and 19.7%, respectively. Underweight was most prevalent in South and Southeast Asia (20%), Central Europe (16.7%) and Turkey (15.2%), whereas overweight and obesity were most common in the Middle East (40%) and the US (33%). BMI SDS at PD initiation was associated positively with current eGFR and gastrostomy feeding prior to PD start. Over the course of PD BMI SDS tended to increase on CPD in underweight and normal weight children, whereas it decreased in initially overweight patients. In infancy, mortality risk was amplified by obesity, whereas in older children mortality was markedly increased in association with underweight. Both underweight and overweight are prevalent in pediatric ESKD, with the prevalence varying across the globe. Late dialysis start is associated with underweight, while enteral feeding can lead to obesity. Nutritional abnormalities tend to attenuate with time on dialysis. Mortality risk appears increased with obesity in infants and with underweight in older children.
Keywords: Asia; Americas; Infant; chronické selhání ledvin; Child, Preschool; Europe; kojenec; dítě; mladiství; Female; Male; Adolescent; Registries; Humans; nadváha; nutriční stav; rizikové faktory; Thinness; mužské pohlaví; peritoneální dialýza; předškolní dítě; Enteral Nutrition; obezita dětí a dospívajících; lidé; Pediatric Obesity; Peritoneal Dialysis; longitudinální studie; Amerika; ženské pohlaví; registrace; enterální výživa; Child; hubenost; prevalence; Overweight; Kidney Failure, Chronic; Prevalence; Asie; Risk Factors; Evropa; Nutritional Status; Longitudinal Studies